THE INFLUENCE OF CAREER DEVELOPMENT ON EMPLOYEE JOB SATISFACTION IN CLASS IIB PURWOKERTO NARCOTICS CORRECTIONAL INSTITUTION - Gunawan, Bagus Indra; Rifani, Denny Nazaria (Universitas Nusa Cendana, 2025)
This study aims to determine the effect of career development on employee job satisfaction at the Class IIB Narcotics Penitentiary Purwokerto. This study uses quantitative research methods with non-probability techniques by applying a saturated sampling of 60 people. The data collection technique was carried out using the distribution of questionnaires to respondents via Google Form. There are 30 statement items that are used as indicators in the study. The data analysis technique used is through the normality test, simple linear regression test, significance test, and determination test which is processed using IBM SPSS software version 25. The results showed that there was an effect of career development on job satisfaction. The results of the determination test obtained with an R Square value of 32.7% on the job satisfaction variable, while the remaining 67.3% is influenced by other variables. Therefore, it can be concluded that there is an influence between career. Keywords: Career Development; Job Satisfaction; Correctional Officer